Elevated resting heart rate as a predictor of inflammation and cardiovascular risk in healthy obese individuals - Al-Rashed, Fatema; Sindhu, Sardar; Al Madhoun, Ashraf; Ahmad, Zunair; AlMekhled, Dawood; Azim, Rafaat; Al-Kandari, Sarah; Wahid, Maziad Al-Abdul; Al-Mulla, Fahd; Ahmad, Rasheed (Scientific reports, 2021)
The role of leukocyte inflammatory markers and toll like receptors (TLRs)2/4 in pathologies associated with elevated resting heart rate (RHR) levels in healthy obese (HO) individuals is not well elucidated. Herein, we investigated the relationship of RHR with expression of leukocyte-inflammatory markers and TLRs in HO individuals. 58-obese and 57-lean participants with no history of a major medical condition, were recruited in this study. In HO individuals, the elevated-RHR correlated positively with diastolic blood pressure, cholesterol, pro-inflammatory monocytes CD11b + CD11c + CD206 − phenotype (r = 0.52, P = 0.0003) as well as with activated T cells CD8 + HLA-DR + phenotype (r = 0.27, P = 0.039). No association was found between RHR and the percentage of CD16 + CD11b + neutrophils. Interestingly, elevated RHR positively correlated with cells expressing TLR4 and TLR2 (CD14 + TLR4 + , r = 0.51, P ≤ 0.0001; and CD14 + TLR2 + , r = 0.42 , P = 0.001). TLR4 + expressing cells also associated positively with the plasma concentrations of proinflammatory or vascular permeability/matrix modulatory markers including TNF-α (r = 0.36, P = 0.005), VEGF (r = 0.47, P = 0.0002), and MMP-9 (r = 0.53, P ≤ 0.0001). Multiple regression revealed that RHR is independently associated with CD14 + TLR4 + monocytes and VEGF. We conclude that in HO individuals, increased CD14 + TLR4 + monocytes and circulatory VEGF levels associated independently with RHR, implying that RHR monitoring could be used as a non-invasive clinical indicator to identify healthy obese individuals at an increased risk of developing inflammation and cardiovascular disease.